2019
DOI: 10.1111/aas.13472
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and CSF‐biomarkers for Alzheimer's disease predict mortality after acute hip fracture

Abstract: Background: Mortality is high after an acute hip fracture (AHF) surgery. Are cognitive impairment and/or altered levels of Alzheimer's Disease (AD)-biomarkers in cerebrospinal fluid (CSF) predictors of mortality in AHF-patients, as retrospective studies indicate? Methods: Prospective single-center study including 373 AHF-patients, operated in spinal anesthesia. Cognitive status was evaluated by clinical dementia rating (CDR);CSF was analyzed for AD-biomarker concentrations (total tau (T-tau), phosphorylated ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…After adjusting for differences between the cohorts, there was a substantially increased risk of death due to cardiovascular, pulmonary, cerebrovascular, and septic events in patients with dementia. The relationship between dementia and postoperative mortality has long been known by orthopedic surgeons [1][2][3][4]. In a meta-analysis by Rao et al from 2016, comparing hospital outcomes in all patients with and without dementia, the authors found that the relative risk of allcause mortality was 70% higher in patients with dementia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After adjusting for differences between the cohorts, there was a substantially increased risk of death due to cardiovascular, pulmonary, cerebrovascular, and septic events in patients with dementia. The relationship between dementia and postoperative mortality has long been known by orthopedic surgeons [1][2][3][4]. In a meta-analysis by Rao et al from 2016, comparing hospital outcomes in all patients with and without dementia, the authors found that the relative risk of allcause mortality was 70% higher in patients with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Labeling the cause of death as dementia obscures this fact and lulls physicians into a false sense of security by promoting the reasoning 'there was nothing more we could have done'. Dementia is a risk factor that predicts mortality, not the end cause [2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, it was proven that dementia predicted one-year mortality for patients with hip fracture. 32 , 33 However, we could not enroll this variable due to the lack of quantitative assessment of preoperative cognitive impairment in the original medical record.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of this study was to observe longitudinal post‐surgical changes to serum neuroprotein concentrations (NFL, tau, Abeta40, 17 Abeta42), in association with concurrent peroperative changes to regional cerebral oxy‐saturation, and to post‐operative cognitive function (by so‐called ISPOCD tests 18 ) which might arise from low cerebral perfusion states in the beach chair position. Therefore, shoulder surgery patients were targeted.…”
Section: Introductionmentioning
confidence: 99%